As indicações geográficas e os possíveis impactos nas relações de consumo no Brasil: uma análise a partir dos vieses da sustentabilidade - Silva, Camila Morás da (2020)
The present study aimed to investigate whether or not the Geographical Indications Institute has the potential to subvert the consumerist logic to meet sustainability biases based on the offer of products recognized by the certification of origin in Brazil. This purpose was due to the need to overcome the reductionist nature of the concepts surrounding production and the impacts of consumption in the current context, a challenge that addresses one of the scopes of the instrument of geographical indications. This, in addition to the fact that Brazil is a country of singular territorial extension, biodiversity and culture, elements that can make possible, from the consolidation of the IGs, a re-reading of the marketing strategies beyond the mere economic nature. Initially, the study aimed to present the normative and conceptual framework of intellectual property in which the Geographical Indications are inserted and to verify, according to the Juarez de Freitas doctrine, to what extent the geographical indications are aligned with the multidimensions of sustainability. In a second step, the scope of the study was to investigate, through the identification of the possible overlapping of geographical indications with the consumer market, the potential of this institute as a differentiating element of goods and products, and, from there, analyze this relationship , its potential and limits in the municipality of Santa Maria / RS. The last stage had been directed to the study of the elements and strategies of use of the geographical indications from the analysis of the concrete effects of the European case. To this end, the research was based on the theory of the systemic-complex base, since it has a transdisciplinary character. The deductive approach was used, considering that it started from the legal premises related to intellectual property and analyzed specific situations in the municipality of Santa Maria, RS and the experience lived in the European Union in order to analyze the possibilities of consolidating the IGs nationwide. The method of procedure used outside the structuralist, since it will analyze the application of the conceptual contributions and legal regulations of the IGs in order to verify their possible impacts on consumer relations in Brazil. Finally, the documentary and bibliographic research technique was applied. It was concluded that geographical indications can act as a legal instrument capable of promoting or influencing change in the current model of production and consumption, given that both the institute and the search for development have in common the interconnection between the multidimensions of sustainability. Thus, this dissertation is fully inserted in the area of concentration of the postgraduate program called Emerging Rights in Global Society, as well as in the line of research on socio-biodiversity and sustainability rights.